The Impact of Private Long-Term Care Insurance on the Use of Long-Term Care - Yong Li; Gail A. Jensen (SAGE Publishing, 2011)
This paper investigates the effects of privately purchased long-term care insurance (LTCI) on three major types of long-term care services: nursing home care, paid home care, and informal care received from family and friends. Using 2002-2008 data from the ongoing Health and Retirement Study, we analyze the determinants of long-term care utilization simultaneously with the determinants of holding LTCI. We find that LTCI has modest effects on the likelihood of using long-term care services. For the very frail elderly, private LTCI enhances their access to nursing home care. For those with moderate disability, LTCI makes it more likely that they can remain at home and receive home care services, instead of going to a nursing home. We find no evidence that formal care substitutes for informal care in the presence of LTCI. These findings suggest that if LTCI becomes much more prevalent in the future, many older adults will be able to choose the type of long-term care arrangement that best suits their needs.